2001
DOI: 10.7863/jum.2001.20.3.197
|View full text |Cite
|
Sign up to set email alerts
|

Low‐intensity pulsed ultrasound initiates bone healing in rat nonunion fracture model.

Abstract: Low-intensity pulsed ultrasound exposure has been shown clinically to shorten the fracture repair process and to induce healing of nonunions in humans, but its mechanism of action remains unclear. In this study we investigated the effect and mechanism of low-intensity pulsed ultrasound on nonunion fracture healing in rat tibias. A consistently reproducible nonunion was produced in rat tibias by muscle interposition without osteotomy. This model was produced by creating a closed tibial fracture with only the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0
8

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(62 citation statements)
references
References 30 publications
(34 reference statements)
1
53
0
8
Order By: Relevance
“…Accelerated healing by ultrasound has also been reported for delayed union and nonunion. Takigawa et al [32] reported that LIPUS promoted healing a the rat nonunion fracture model, and Mayer et al [18] reported that LIPUS therapy holds great promise for treatment-resistant nonunion and delayed union.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accelerated healing by ultrasound has also been reported for delayed union and nonunion. Takigawa et al [32] reported that LIPUS promoted healing a the rat nonunion fracture model, and Mayer et al [18] reported that LIPUS therapy holds great promise for treatment-resistant nonunion and delayed union.…”
Section: Discussionmentioning
confidence: 99%
“…including the use of mechanical stress [4,5,11], transplantation of cultured cells [ 12,26,33], and pharmacolLow-intensity pulsed ultrasound (LIPUS) has been found to stimulate the healing of fresh fracture, nonunion and delayed union in animal models and in clinical treatment [13,17,18,32]. There also have been some reports that LJPUS accelerates bone maturation in distraction osteogenesis in animal models [ 19,291.…”
Section: Introductionmentioning
confidence: 99%
“…US was found to have the effects of increasing cell proliferation and accelerating bone consolidation after a fracture, and increasing the mechanical strength of the bone callus in rats and rabbits (12,13) . Takikawa et al (12) observed in an experimental study that, after six weeks of US treatment, it had significantly increased the consolidation rate in fractures with bone nonunion, compared with the control group. The same results were found by Sun et al (14) and Lirani et al (15) .…”
Section: Comparative Study Of the Effects Of Low-level Laser And Lowmentioning
confidence: 99%
“…Os resultados obtidos neste estudo para o grupo não suspenso (G1) concordam com Carvalho e Cliquet Jr 20 , que, analisando a ação do US pulsado de baixa intensidade durante 20 dias consecutivos por 20 minutos diários na região proximal dos fêmures de ratas osteopênicas, evidenciaram melhora da arquitetura dos ossos (análise qualitativa), mas não do conteúdo mineral (análise quantitativa), supondo que a análise quantitativa não tenha apontado diferenças devido ao fato de existir grande quantidade de tecido neoformado, o qual ainda não está totalmente mineralizado. Os autores comentam que a duração do tratamento com US de baixa intensidade talvez não tenha sido suficiente para possibilitar a total mineralização das regiões estimuladas, o que não gerou alterações de forma quantitativa, fato que pode ter influenciado os resultados do presente trabalho, uma vez que usamos somente análise quantitativa, além de termos utilizado menor tempo de tratamento quando comparados com outros estudos [21][22][23] .…”
Section: Discussionunclassified